(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
The paper presents a study of formation of the primary particle size distribution in suspension “powder” polymerization of vinyl chloride. The process is modelled by means of a population balance model, and the primary particle size distribution inside the polymerizing monomer droplets is determined by analysing the population balance equation, governing the nucleation, growth, and aggregation of the primary particles, using the moment method. The infinite set of moment equations obtained by moment transformation was closed using a sum aggregation kernel, and for numerical experimentation a second order moment equation model was used. The results show how important are to choose the correct parameters in production of poly(vinyl chloride) by suspension polymerization. Changing the parameters a bit the quality of product may change significantly. The results presented in the paper illustrate well that the population balance model can be used for describing the process and a number its properties with sufficient accuracy.